Flexible aqueous binder for negative electrode of lithium battery and preparation method of flexible aqueous binder
By introducing flexible polyurethane spherical microstructures and long-chain alkyl structures into polyacrylic acid binders, the problems of flexibility and brittleness of water-based polyacrylic acid binders have been solved, improving the processing performance and electrolyte resistance of the electrode sheets and enabling green and environmentally friendly large-scale production.
Patent Information
- Application Number
- CN202511005131.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-21
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2045-07-21
AI Technical Summary
Existing water-based polyacrylic acid binders have poor flexibility and high brittleness, making the electrode sheets prone to cracking and affecting processing performance.
By introducing a flexible polyurethane spherical microstructure into the linear structure of polyacrylic acid polymer and using a long-chain alkyl structure as the main body, a flexible waterborne adhesive with crosslinking sites is prepared, realizing both "point-to-point" and "point-to-line" bonding methods, reducing the use of ester groups and ether bonds.
It improves the processing performance of the electrode, enhances the flexibility and electrolyte resistance of the binder, and reduces the brittleness and cracking risk of the electrode. The preparation process is green and environmentally friendly and easy to scale up.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer material synthesis technology, specifically relating to a flexible aqueous binder for lithium battery anodes and its preparation method. Background Technology
[0002] In recent years, with the increasing demand for clean energy in my country, lithium batteries, as an energy carrier with high energy density and good cycle life, have played an important role in electric vehicles and large-scale energy storage equipment. Electrodes, as an important component of lithium batteries, are prepared by bonding conductive materials to a metal current collector using a small amount of binder. In actual production, the binders for the positive and negative electrodes of lithium batteries are mainly aqueous binders (such as styrene-butadiene emulsion, polyacrylic acid, etc.) and oil-based binders (such as solvent-based PVDF, etc.), with aqueous binders mostly used for bonding the active material of the negative electrode.
[0003] Currently, styrene-butadiene emulsion (SBR) and polyacrylic acid binders are widely used in negative electrode binders. SBR has been used in battery negative electrode binder applications for a long time. Its microscopic bonding with the electrode active material is a "point-to-point" bonding method, resulting in electrodes with excellent flexibility and good cutting and processing performance. However, it still suffers from a decrease in adhesion after long-term electric cycling, leading to electrode structure collapse. With increasingly higher requirements for lithium battery energy density and electric cycling performance, polyacrylic acid binders are becoming more widely used. Because of its linear molecular structure, polyacrylic acid binders exhibit a "point-to-line" bonding with the electrode active material, resulting in superior adhesion and electric cycling performance. For example, CN112680147B discloses a method for preparing a battery adhesive, using acrylate or acrylamide monomers and an initiator through solution polymerization. This water-based binder has strong adhesion, and the prepared electrodes exhibit stable cycle performance and high capacity. CN115050963B discloses a binder for the negative electrode of a lithium-ion battery, its preparation method and uses. This invention prepares a negative electrode binder with excellent electrolyte resistance through a core-shell emulsion polymerization method.
[0004] Although the aforementioned waterborne polyacrylic acid binders offer excellent electrolyte resistance and bonding performance, they still suffer from poor flexibility, high brittleness, and a tendency for electrode sheets to crack and shed powder, severely impacting subsequent electrode processing. Therefore, developing a preparation route for a flexible waterborne polyacrylic acid binder has significant market and application value. Summary of the Invention
[0005] The purpose of this invention is to solve the problems of poor flexibility and poor subsequent processing performance of existing waterborne polyacrylic acid binders, and to provide a flexible waterborne polyacrylic acid binder for lithium battery anodes and its preparation method.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] A flexible water-based binder for lithium battery anodes, the flexible water-based binder comprising, by weight, 10-80 parts of water-based polyurethane prepolymer, 15-100 parts of water-soluble monomer, 2-40 parts of oil-soluble monomer, 0.1-3 parts of functional monomer, 0.01-1.6 parts of initiator, 5-20 parts of pH adjuster, and 80-500 parts of deionized water;
[0008] The waterborne polyurethane prepolymer comprises, by weight, 20-60 parts of hydroxyl-terminated polybutadiene, 5-50 parts of isocyanate, 0.2-5 parts of hydrophilic chain extender, 0.4-10 parts of hydroxy acrylate, 0.002-0.1 parts of catalyst, 0-20 parts of diluent, 0.2-5 parts of neutralizer, and 30-200 parts of deionized water.
[0009] Furthermore, the water-soluble monomer includes one or more of carboxylic acid monomers, amide monomers, sulfonic acid monomers, and vinylpyrrolidone;
[0010] The oil-soluble monomer includes one or more of alkyl methacrylate, methylstyrene, methacrylonitrile, alkyl acrylate, styrene, and acrylonitrile, preferably styrene;
[0011] The functional monomers include one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, glycidyl methacrylate, glycidyl acrylate, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, and N-hydroxypropylacrylamide, preferably hydroxyethyl acrylate and hydroxybutyl acrylate.
[0012] The initiator is a persulfate;
[0013] The pH adjuster includes one or more of alkali metal hydroxides and ammonia water, preferably sodium hydroxide.
[0014] Further, the carboxylic acid monomer is one or more of acrylic acid, methacrylic acid, itaconic acid, β-carboxyethyl acrylic acid, maleic acid and their corresponding salts; the amide monomer is a vinyl-containing amide monomer; the sulfonic acid monomer is one or more of methpropylene sulfonic acid, propylene sulfonic acid and their corresponding salts, preferably carboxylic acid and amide, more preferably acrylic acid, methacrylic acid and acrylamide.
[0015] Furthermore, the vinyl-containing amide monomer is one or more of acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide.
[0016] Furthermore, the persulfate is one or more of ammonium persulfate, potassium persulfate, and sodium persulfate, with ammonium persulfate being preferred.
[0017] Furthermore, the hydroxyl-terminated polybutadiene includes hydrogenated hydroxyl-terminated polybutadiene and / or non-hydrogenated hydroxyl-terminated polybutadiene, preferably hydrogenated hydroxyl-terminated polybutadiene, and more preferably, the molecular weight of Mn is between 2000 and 6000.
[0018] The isocyanate includes one or more of isophorone diisocyanate, hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate, preferably isophorone diisocyanate;
[0019] The hydrophilic chain extender includes one or more of dimethylolpropionic acid, dimethylolbutyric acid, sodium ethylenediaminoethanesulfonate, N,N-dihydroxyethylalanine, 3,4-dihydroxybutyric acid, and 3,6-dihydroxy-2-toluenesulfonic acid, preferably dimethylolpropionic acid or dimethylolbutyric acid.
[0020] The hydroxy acrylate includes one or more of hydroxyethyl acrylate, hydroxypropyl acrylate and hydroxybutyl acrylate, preferably hydroxyethyl acrylate and hydroxybutyl acrylate;
[0021] The catalyst is an organometallic catalyst;
[0022] The diluent includes one or more of acetone, methyl ethyl ketone, N-methylpyrrolidone (NMP), and N,N-dimethylmethylmethylamide, preferably acetone;
[0023] The neutralizing agent comprises one or more of the following: tertiary amine compounds, N,N-dialkylalkanolamines, trialkylalkanolamines, inorganic alkali metal salts, and ammonia. Triethylamine is preferred among the tertiary amine compounds.
[0024] Furthermore, the organometallic catalyst is dibutyltin dilaurate (DBTL) or stannous octoate, preferably dibutyltin dilaurate.
[0025] Further, the tertiary amine compound is one or more of trialkylamine, trimethylamine, triethylamine, and tributylamine; the N,N-dialkylalkanolamine is one or more of N,N-dimethylethanolamine, N,N-dimethylpropanolamine, N,N-dipropylethanolamine, and 1-dimethylamino-2-methyl-2-propanol; the trialkylolamine is triethanolamine; and the inorganic alkali metal salt is potassium hydroxide or sodium hydroxide.
[0026] A method for preparing the above-mentioned flexible aqueous binder for lithium battery negative electrode, the method comprising the following steps:
[0027] (1) Weigh hydroxyl-terminated polybutadiene and place it in a reaction vessel with a stirrer. After vacuum dehydration at 110~120℃ for 2 hours, cool down to 50℃ and add isocyanate and catalyst. Heat up to 60~80℃ and react until the content of -NCO groups reaches the theoretical value (determined by di-n-butylamine titration). Then add a hydrophilic chain extender and react until the content of -NCO groups reaches the theoretical value (add diluent in a timely manner during the reaction to adjust the viscosity of the system). Then add hydroxy acrylate and react until there are no -NCO groups in the system. Finally, slowly disperse it into deionized water containing a neutralizing agent under high-speed shear force. If a diluent is added during the preparation process, the diluent is removed by vacuum evaporation to obtain vinyl-terminated waterborne polyurethane prepolymer, which is stored for later use.
[0028] (2) Weigh out a portion of the water-soluble monomers (70-90% of the total amount), and mix all the oil-soluble monomers and functional monomers in the dropping kettle 1 for later use; prepare an initiator aqueous solution and place it in the dropping kettle 2 for later use.
[0029] (3) Accurately weigh the remaining water-soluble monomer and deionized water and place them in the reaction vessel. Heat the vessel to 82~85℃, add the remaining initiator, and react for 20~40 min. Then, simultaneously add the monomer from dropper 1 and the initiator aqueous solution from dropper 2 in step (2). The addition time is 0.5~4 h. After the addition is completed, keep the vessel at 82~85℃ for 30~60 min.
[0030] (4) After the heat preservation is completed, accurately weigh the waterborne polyurethane prepolymer prepared in step (1) and add it dropwise into the reactor. The dropwise addition time is 15~60min. After the dropwise addition is completed, continue to keep warm for 1~5h.
[0031] (5) After the heat preservation is completed, the temperature is lowered to below 50°C, and a pH adjuster is added to adjust the pH to 7~9 to obtain a flexible water-based adhesive.
[0032] Further, in step (2), the water-soluble monomer accounts for 70% to 90% of the total water-soluble monomer, and in the initiator aqueous solution, the initiator used accounts for 60% to 80% of the total initiator, and the water used accounts for 5% to 30% of the total.
[0033] The advantages of this invention over the prior art are as follows:
[0034] (1) This invention introduces a flexible polyurethane spherical microstructure into the linear structure of polyacrylic acid polymer, so as to achieve two bonding methods of "point-to-point" and "point-to-line" between the binder and the active material of the electrode in the microstructure. This significantly improves the poor phenomena such as the high brittleness of polyacrylic acid binder and the easy cracking of the electrode surface, and improves the processing performance of the electrode.
[0035] (2) The present invention uses terminal hydroxyl polybutadiene with long-chain alkyl structure as the main structure, which effectively avoids the adverse effects of the introduction of a large number of ester groups and ether bond structure on the electrolyte resistance of the adhesive, and effectively takes into account the flexibility and high temperature electrolyte resistance of the adhesive.
[0036] (3) The adhesive preparation method provided by the present invention is green and environmentally friendly, does not use a large amount of organic solvents, and is easy to scale up. Detailed Implementation
[0037] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] This invention provides a molecular structure design and preparation method for a flexible waterborne polyacrylic acid adhesive. This method introduces a flexible polyurethane spherical microstructure into the linear structure of the polyacrylic acid polymer, preparing an adhesive with flexible crosslinking sites. This allows the adhesive and the active electrode material to achieve both "point-to-point" and "point-to-line" bonding at the microstructure, significantly improving the high brittleness and poor cutting and winding performance of polyacrylic acid adhesives. Furthermore, the flexible prepolymer structure prepared by this method is predominantly a long-chain alkyl structure, with no ether bonds and few ester groups in the molecular structure. Therefore, the introduction of this flexible structure does not reduce the adhesive's electrolyte resistance.
[0039] The technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0040] Example 1
[0041] (1) First, accurately weigh 35g of hydrogenated hydroxyl-terminated polybutadiene (Mn2000) and place it in a reaction vessel with a stirrer. After vacuum dehydration at 120℃ for 2h, cool to 50℃ and add 7.5g of isophorone diisocyanate and 0.01g of dibutyltin dilaurate. Heat to 80℃ and react until the -NCO group content reaches the theoretical value (determined by di-n-butylamine titration). Then add 1.7g of dimethylolpropionic acid and react until the -NCO group content reaches the theoretical value (add diluent as needed during the reaction to adjust the viscosity of the system). Then add 1.5g of hydroxybutyl acrylate and react until there are no -NCO groups in the system. Finally, slowly disperse it into 120g of 3wt% triethylamine aqueous solution under high-speed shear force. Remove the diluent under reduced pressure to obtain vinyl-terminated waterborne polyurethane prepolymer, which is stored for later use.
[0042] (2) Accurately weigh 60g of acrylic acid, 4g of butyl acrylate and 1g of hydroxyethyl acrylate and place them in drop container 1 and mix them evenly for later use; accurately weigh 0.08g of ammonium persulfate and 15g of deionized water and place them in drop container 2 for later use.
[0043] (3) Accurately weigh 10g of acrylic acid and 110g of deionized water and place them in a reaction vessel. Heat the vessel to 82℃ and add 0.03g of ammonium persulfate. After reacting for 20min, simultaneously add the monomer from dropper 1 and the initiator solution from dropper 2 in step (1) for 1.5h. After the addition is complete, keep the vessel at 85℃ for 30min.
[0044] (4) After the heat preservation is completed, accurately weigh 60g of the prepolymer prepared in step (1) and add it dropwise into the reactor. The dropwise addition time is 40min. After the dropwise addition is completed, continue to keep warm for 2h.
[0045] (5) After the heat preservation is completed, the temperature is lowered to below 50°C, and a pH adjuster is added to adjust the pH to 7~9 to obtain a flexible water-based adhesive.
[0046] Example 2
[0047] (1) First, accurately weigh 48g of hydrogenated hydroxyl-terminated polybutadiene (Mn3000) and place it in a reaction vessel with a stirrer. After vacuum dehydration at 120℃ for 2h, cool to 50℃ and add 7.2g of isophorone diisocyanate and 0.03g of dibutyltin dilaurate. Heat to 80℃ and react until the -NCO group content reaches the theoretical value (determined by di-n-butylamine titration). Then add 1.7g of dimethylolpropionic acid and react until the -NCO group content reaches the theoretical value (add diluent as needed during the reaction to adjust the viscosity of the system). Then add 1.2g of hydroxyethyl acrylate and react until there are no -NCO groups in the system. Finally, slowly disperse it into 120g of 3% triethylamine aqueous solution under high-speed shear force. Remove the diluent under reduced pressure to obtain vinyl-terminated waterborne polyurethane prepolymer, which is stored for later use.
[0048] (2) Accurately weigh 50g of acrylic acid, 10g of methacrylic acid, 2g of styrene and 1g of hydroxybutyl acrylate and place them in drop container 1 and mix them evenly for later use; accurately weigh 0.06g of ammonium persulfate and 15g of deionized water and place them in drop container 2 for later use.
[0049] (3) Accurately weigh 10g of acrylic acid, 2g of methacrylic acid and 110g of deionized water and place them in a reaction vessel. Heat the vessel to 82℃, add 0.02g of ammonium persulfate, and react for 20min. Then, simultaneously add the monomer from dropper 1 and the initiator solution from dropper 2 in step (1) for 1.5h. After the addition is complete, keep the vessel at 85℃ for 30min.
[0050] (4) After the heat preservation is completed, accurately weigh 40g of the prepolymer prepared in step (1) and add it dropwise into the reactor. The dropwise addition time is 40min. After the dropwise addition is completed, continue to keep warm for 2h.
[0051] (5) After the heat preservation is completed, the temperature is lowered to below 50°C, and a pH adjuster is added to adjust the pH to 7~9 to obtain a flexible water-based adhesive.
[0052] Example 3
[0053] (1) First, accurately weigh 55g of hydrogenated hydroxyl-terminated polybutadiene (Mn5000) and place it in a reaction vessel with a stirrer. After vacuum dehydration at 120℃ for 2h, cool to 50℃ and add 4.9g of isophorone diisocyanate and 0.03g of dibutyltin dilaurate. Heat to 80℃ and react until the -NCO group content reaches the theoretical value (determined by di-n-butylamine titration). Then add 1.7g of dimethylolpropionic acid and react until the -NCO group content reaches the theoretical value (add diluent as needed during the reaction to adjust the viscosity of the system). Then add 1.2g of hydroxyethyl acrylate and react until there are no -NCO groups in the system. Finally, slowly disperse it into 120g of 3% triethylamine aqueous solution under high-speed shear force. Remove the diluent under reduced pressure to obtain vinyl-terminated waterborne polyurethane prepolymer, which is stored for later use.
[0054] (2) Accurately weigh 37g of acrylic acid, 12g of methacrylic acid, 11g of acrylamide, 5g of acrylonitrile and 1.2g of hydroxybutyl acrylate and place them in drop container 1 and mix them evenly for later use; accurately weigh 0.06g of ammonium persulfate and 15g of deionized water and place them in drop container 2 for later use.
[0055] (3) Accurately weigh 8g of acrylic acid, 2g of methacrylic acid, 0.5g of acrylonitrile and 110g of deionized water and place them in a reaction vessel. Heat the mixture to 82℃, add 0.03g of ammonium persulfate, and react for 20min. Then, simultaneously add the monomer from dropper 1 and the initiator solution from dropper 2 in step (1) for 1.5h. After the addition is complete, keep the mixture at 85℃ for 30min.
[0056] (4) After the heat preservation is completed, accurately weigh 40g of the prepolymer prepared in step (1) and add it dropwise into the reactor. The dropwise addition time is 40min. After the dropwise addition is completed, continue to keep warm for 2h.
[0057] (5) After the heat preservation is completed, the temperature is lowered to below 50°C, and a pH adjuster is added to adjust the pH to 7~9 to obtain a flexible water-based adhesive.
[0058] Example 4
[0059] (1) First, accurately weigh 30g of hydrogenated hydroxyl-terminated polybutadiene (Mn1000) and place it in a reaction vessel with a stirrer. After vacuum dehydration at 120℃ for 2h, cool to 50℃ and add 13.3g of isophorone diisocyanate and 0.01g of dibutyltin dilaurate. Heat to 80℃ and react until the -NCO group content reaches the theoretical value (determined by di-n-butylamine titration). Then add 1.7g of dimethylolpropionic acid and react until the -NCO group content reaches the theoretical value (add diluent as needed during the reaction to adjust the viscosity of the system). Then add 1.5g of hydroxybutyl acrylate and react until there are no -NCO groups in the system. Finally, slowly disperse it into 120g of 3% triethylamine aqueous solution under high-speed shear force. Remove the diluent under reduced pressure to obtain vinyl-terminated waterborne polyurethane prepolymer, which is stored for later use.
[0060] (2) Accurately weigh 40g of acrylic acid, 20g of acrylamide, 5g of acrylonitrile and 1.2g of hydroxybutyl acrylate and place them in drop container 1 and mix them evenly for later use; accurately weigh 0.06g of ammonium persulfate and 15g of deionized water and place them in drop container 2 for later use.
[0061] (3) Accurately weigh 12g of acrylic acid, 1.5g of acrylonitrile and 110g of deionized water and place them in a reaction vessel. Heat to 82℃, add 0.03g of ammonium persulfate, and react for 20min. Then, simultaneously add the monomer from dropping vessel 1 and the initiator solution from dropping vessel 2 in step (1) for 1.5h. After the addition is complete, keep warm at 85℃ for 30min.
[0062] (4) After the heat preservation is completed, accurately weigh 40g of the prepolymer prepared in step (1) and add it dropwise into the reactor. The dropwise addition time is 40min. After the dropwise addition is completed, continue to keep warm for 2h.
[0063] (5) After the heat preservation is completed, the temperature is lowered to below 50°C, and a pH adjuster is added to adjust the pH to 7~9 to obtain a flexible water-based adhesive.
[0064] Comparative Example
[0065] This comparative example was prepared using a traditional solution polymerization method, and the steps are as follows:
[0066] (1) Accurately weigh 30g acrylic acid, 10g methacrylic acid, 7g acrylamide, 8g acrylonitrile and 1.2g hydroxybutyl acrylate and place them in drop container 1 and mix them evenly for later use; accurately weigh 0.05g ammonium persulfate and 15g deionized water and place them in drop container 2 for later use.
[0067] (2) Accurately weigh 10g of acrylic acid, 2g of methacrylic acid, 0.5g of acrylonitrile and 110g of deionized water and place them in a reaction vessel. Heat the vessel to 82℃, add 0.03g of ammonium persulfate, and react for 20min. Then, simultaneously add the monomer from dropping vessel 1 and the initiator solution from dropping vessel 2 in step (1) for 1.5h. After the addition is complete, keep the vessel at 85℃ for 2h.
[0068] (3) After the heat preservation is completed, the temperature is lowered to below 50°C, and a pH adjuster is added to adjust the pH to 7~9 to obtain the water-based adhesive.
[0069] The water-based adhesive obtained above was subjected to electrolyte and slurry resistance tests:
[0070] ① Electrolyte Swelling and Precipitation Resistance Test: The prepared aqueous adhesive solution was dried at 120℃ for 1 hour, and its weight was recorded as W0. Then, it was placed in an electrolyte solution at 60℃ and kept at that temperature for 72 hours. After that, it was removed, the surface electrolyte was wiped clean, and its weight was recorded as W1. Finally, it was placed in a 200℃ oven and dried for 4 hours, and its weight was recorded as W2. The swelling rate and precipitation rate of the electrolyte resistance were calculated according to the following formulas. The test results are shown in Table 1.
[0071] Swelling rate (%) = (W1 - W0) / W0 × 100%
[0072] Extraction rate (%) = (W2 - W0) / W0 × 100%
[0073] ② Adhesion strength measurement
[0074] Using the binders from the above examples and comparative examples, negative electrode sheets were prepared, and their 180° peel strength was measured. The specific method is as follows: 98.5g of artificial graphite and 1.5g of binder, used as the negative electrode active material, were added to 100g of deionized water and dispersed evenly to obtain a negative electrode mixture slurry. This negative electrode mixture slurry was coated onto a 12μm thick copper foil, then dried and rolled. An areal density of 20mg / cm³ was formed. 2 Compacted density 1.60 g / cm³ 3 The negative electrode sheet was then attached to the surface of the negative electrode using 3M standard tape (Scotch 600 / 25mm), and rolled back and forth three times with a roller. After being placed under standard conditions for 20 minutes, a peel force test was performed. The test results are shown in Table 1.
[0075] ③ Electrode flexibility test
[0076] The prepared negative electrode sheet was cut into strips of 150mm × 10mm and placed at a temperature of 25±2℃ and a humidity of In a 30% environment, the device was fixed on a bending tester and bent 180° with a radius of 5mm. The number of bends at which cracks or peeling of the active layer occurred was recorded. The test results are shown in Table 1.
[0077] Table 1. Test results of the resistance of water-based adhesives to electrolytes and slurries.
[0078]
[0079] As can be seen from Table 1, by introducing a long alkyl chain flexible structure to construct a novel "point-line" micro-bonding method, this invention significantly improves the problem of high brittleness and easy cracking of polyacrylic acid adhesive, and further enhances the adhesive strength to active materials and the adhesion to the electrode sheet; in addition, the introduction of the flexible structure does not have a significant adverse effect on the electrolyte resistance of the adhesive.
[0080] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A flexible aqueous binder for lithium battery negative electrodes, characterized in that: The flexible waterborne adhesive comprises, by weight, 10-80 parts of waterborne polyurethane prepolymer, 15-100 parts of water-soluble monomer, 2-40 parts of oil-soluble monomer, 0.1-3 parts of functional monomer, 0.01-1.6 parts of initiator, 5-20 parts of pH adjuster, and 80-500 parts of deionized water. The waterborne polyurethane prepolymer comprises, by weight, 20-60 parts of hydroxyl-terminated polybutadiene, 5-50 parts of isocyanate, 0.2-5 parts of hydrophilic chain extender, 0.4-10 parts of hydroxy acrylate, 0.002-0.1 parts of catalyst, 0-20 parts of diluent, 0.2-5 parts of neutralizer, and 30-200 parts of deionized water.
2. The flexible aqueous binder for lithium battery negative electrode according to claim 1, characterized in that: The water-soluble monomers include one or more of carboxylic acid monomers, amide monomers, sulfonic acid monomers, and vinylpyrrolidone; The oil-soluble monomers include one or more of alkyl methacrylate, methylstyrene, methacrylonitrile, alkyl acrylate, styrene, and acrylonitrile; The functional monomers include one or more of the following: hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, glycidyl methacrylate, glycidyl acrylate, N-hydroxymethyl acrylamide, N-hydroxyethyl acrylamide, and N-hydroxypropyl acrylamide. The initiator is a persulfate; The pH adjuster includes one or more of alkali metal hydroxides and ammonia.
3. The flexible aqueous binder for lithium battery negative electrode according to claim 2, characterized in that: The carboxylic acid monomers are one or more of acrylic acid, methacrylic acid, itaconic acid, β-carboxyethyl acrylic acid, maleic acid, and their corresponding salts; the amide monomers are vinyl-containing amide monomers; and the sulfonic acid monomers are one or more of methpropylene sulfonic acid, propylene sulfonic acid, and their corresponding salts.
4. The flexible aqueous binder for lithium battery negative electrode according to claim 3, characterized in that: The vinyl-containing amide monomer is one or more of acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide.
5. The flexible aqueous binder for lithium battery negative electrode according to claim 2, characterized in that: The persulfates are one or more of ammonium persulfate, potassium persulfate, and sodium persulfate.
6. The flexible aqueous binder for lithium battery negative electrode according to claim 1, characterized in that: The hydroxyl-terminated polybutadiene includes hydrogenated hydroxyl-terminated polybutadiene and / or non-hydrogenated hydroxyl-terminated polybutadiene. The isocyanate includes one or more of isophorone diisocyanate, hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate; The hydrophilic chain extender includes one or more of dimethylolpropionic acid, dimethylolbutyric acid, sodium ethylenediaminoethanesulfonate, N,N-dihydroxyethylalanine, 3,4-dihydroxybutyric acid, and 3,6-dihydroxy-2-toluenesulfonic acid; The hydroxyacrylates include one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxybutyl acrylate; The catalyst is an organometallic catalyst; The diluent includes one or more of acetone, methyl ethyl ketone, N-methylpyrrolidone (NMP), and N,N-dimethylmethylmethylamide; The neutralizing agent includes one or more of the following: tertiary amine compounds, N,N-dialkylalkanolamines, trialkylalkanolamines, inorganic alkali metal salts, and ammonia.
7. A flexible aqueous binder for lithium battery negative electrodes according to claim 6, characterized in that: The organometallic catalyst is dibutyltin dilaurate (DBTL) or stannous octoate.
8. The flexible aqueous binder for lithium battery negative electrode according to claim 6, characterized in that: The tertiary amine compound is one or more of trialkylamine, trimethylamine, triethylamine, and tributylamine; the N,N-dialkylalkanolamine is one or more of N,N-dimethylethanolamine, N,N-dimethylpropanolamine, N,N-dipropylethanolamine, and 1-dimethylamino-2-methyl-2-propanol; the trialkylalkanolamine is triethanolamine; and the inorganic alkali metal salt is potassium hydroxide or sodium hydroxide.
9. A method for preparing a flexible aqueous binder for a lithium battery negative electrode according to any one of claims 1 to 8, characterized in that: The method includes the following steps: (1) Weigh hydroxyl-terminated polybutadiene and place it in a reaction vessel with a stirrer. After vacuum dehydration at 110~120℃ for 2 hours, cool down to 50℃ and add isocyanate and catalyst. Heat up to 60~80℃ and react until the content of -NCO groups reaches the theoretical value (determined by di-n-butylamine titration). Then add a hydrophilic chain extender and react until the content of -NCO groups reaches the theoretical value (add diluent in a timely manner during the reaction to adjust the viscosity of the system). Then add hydroxy acrylate and react until there are no -NCO groups in the system. Finally, slowly disperse it into deionized water containing a neutralizing agent under high-speed shear force. If a diluent is added during the preparation process, the diluent is removed by vacuum evaporation to obtain vinyl-terminated waterborne polyurethane prepolymer, which is stored for later use. (2) Weigh out a portion of the water-soluble monomers (70-90% of the total amount), and mix all the oil-soluble monomers and functional monomers in the dropping kettle 1 for later use; prepare an initiator aqueous solution and place it in the dropping kettle 2 for later use. (3) Accurately weigh the remaining water-soluble monomer and deionized water and place them in the reaction vessel. Heat the vessel to 82~85℃, add the remaining initiator, and react for 20~40 min. Then, simultaneously add the monomer from dropper 1 and the initiator aqueous solution from dropper 2 in step (2). The addition time is 0.5~4 h. After the addition is completed, keep the vessel at 82~85℃ for 30~60 min. (4) After the heat preservation is completed, accurately weigh the waterborne polyurethane prepolymer prepared in step (1) and add it dropwise into the reactor. The dropwise addition time is 15~60min. After the dropwise addition is completed, continue to keep warm for 1-5h. (5) After the heat preservation is completed, the temperature is lowered to below 50°C, and a pH adjuster is added to adjust the pH to 7~9 to obtain a flexible water-based adhesive.
10. A method for preparing a flexible aqueous binder for a lithium battery negative electrode according to claim 9, characterized in that: In step (2), the water-soluble monomer accounts for 70% to 90% of the total water-soluble monomer, and the initiator aqueous solution contains 60% to 80% of the total initiator and 5% to 30% of the total water.
Citation Information
Patent Citations
A method for preparing a battery adhesive
CN112680147B
A binder for lithium ion battery negative electrode and its preparation method and use
CN115050963B
Binder for lithium ion secondary battery, preparation method and negative pole piece
CN117164768A
Waterborne polyurethane adhesive as well as preparation method and application thereof
CN118290661A
Preparation method of safe high-viscosity carbon-coated aluminum foil current collector for lithium battery
CN118553920A
Cited By
Adhesive emulsion containing core-shell microspheres and preparation method thereof
CN121518068A
A core-shell microsphere-containing adhesive emulsion and a method for preparing the same
CN121518068B
Low-modulus acrylic acid negative electrode adhesive and preparation method thereof
CN121718311A
A low modulus acrylic negative adhesive and a method of making the same
CN121718311B